Regulation of State Ownership Rights Over Land in The National Agrarian Legal System - Mustaqim, Mustaqim; Mega Wijaya, Mustika; Sari Fitria, Mayzara (Faculty of Law, Universitas Pekalongan, 2025)
State control over land is a fundamental principle in Indonesia's national agrarian legal system, which is based on Article 33 paragraph (3) of the 1945 Constitution and elaborated in Law No. 5 of 1960 concerning Basic Agrarian Principles (UUPA). The state, as the holder of state ownership rights over land, has the authority to regulate the allocation, use, and ownership of land for the greatest prosperity of the people. This study aims to analyze the legal provisions regarding state ownership rights and examine their implementation in land management practices in Indonesia. The research method used is normative legal analysis with a legislative and doctrinal approach. The results of the study indicate that although the regulation of state control rights has been legally regulated through the UUPA and its derivative regulations, in practice, various problems are still found, such as overlapping claims, agrarian conflicts, and weak protection of the rights of indigenous peoples and farmers. Therefore, it is necessary to strengthen regulations and the implementation of agrarian justice principles so that state control rights truly function for the welfare of the people.